The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.2527/1991.692433x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of animal and supplement characteristics on average daily gain of grazing beef cattle.

Abstract: Effects of animal gender and age, use of a growth stimulant, and supplementation with grain alone or grain plus other substances on ADG by growing beef cattle grazing bermudagrass paddocks with sod-seeded rye, wheat, and ryegrass were determined. Two grazing experiments (Exp. 1: late winter through mid-spring; Exp. 2: late spring through mid-summer) were conducted. Experiment 1 used 96, 12- to 13-mo-old Simmental-cross calves (heifers, 240 kg; steers, 272 kg), half of which were implanted with zeranol. Within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
1
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 12 publications
2
7
1
1
Order By: Relevance
“…Supplementing Simmental crossbred heifers and steers grazing bermudagrass with a mixture of 60.6% feather meal, 28.3% corn gluten meal and 11.1% blood meal (0.063% of BW) in addition to supplemental corn (0.437% of BW) only nominally (P . 0.05) enhanced daily gain up to 0.75 kg compared with 0.69 kg for corn supplemented (0.437% of BW) animals (Goetsch et al, 1991). Similar results from the same authors were reported when only crossbred steers were involved in another experiment.…”
Section: Supplementation Of Grazing Double-muscled Heiferssupporting
confidence: 78%
See 2 more Smart Citations
“…Supplementing Simmental crossbred heifers and steers grazing bermudagrass with a mixture of 60.6% feather meal, 28.3% corn gluten meal and 11.1% blood meal (0.063% of BW) in addition to supplemental corn (0.437% of BW) only nominally (P . 0.05) enhanced daily gain up to 0.75 kg compared with 0.69 kg for corn supplemented (0.437% of BW) animals (Goetsch et al, 1991). Similar results from the same authors were reported when only crossbred steers were involved in another experiment.…”
Section: Supplementation Of Grazing Double-muscled Heiferssupporting
confidence: 78%
“…2. The significant effect of the protein supplement in our experiment is in contradiction with the results of Goetsch et al (1991), but can be explained by the higher protein requirement of double-muscled animals (Fiems et al, 1998). Consequently, there was a greater response to the extra protein in our experiment.…”
Section: Supplementation Of Grazing Double-muscled Heiferscontrasting
confidence: 56%
See 1 more Smart Citation
“…Conforme citado por GOETSCH et al (1991), a suplementação de animais mantidos em pastagem com alimentos rapidamente fermentáveis no rúmen pode melhorar o desempenho animal por meio de melhor aproveitamento do nitrogênio da forragem, incremento da produção de proteína microbiana e aumento do propionato e o total de ácidos graxos voláteis. Também, segundo PASCOAL e RESTLE (1998), os concentrados energéticos, por apresentarem alto teor de MS, alta velocidade de passagem pelo rúmen, alta digestibilidade e boa palatabilidade, podem favorecer o desempenho animal.…”
Section: Introductionunclassified
“…As previously mentioned, Southeastern cattle operations add cheap gain by utilizing high quality cool season forages. Supplementing forage has been shown to improve gain on multiple occasions (Coelman et al, 1976;Goetsch et al, 1991;Moore et al, 1999;Scholljegerdes and Kronberg, 2010).…”
mentioning
confidence: 99%